ABDULLA AVLONI - Abdurakhmonova Shahzodakhan Pazliddin kizi (Galaxy International Interdisciplinary Research Journal, 2021)
Abdullah Avloni is a great representative of our national spirituality. He is known as the leader of the Jadid movement in Turkestan. Abdullah Avloni is a person who has devoted himself to the education of the children of the nation, the training of leading scientists and specialists, the liberation and prosperity of the country. Here are some of his thoughts:"Education should start from birth, strengthen our body, strengthen our morals, develop our mind".